Computation modelling studies of titanium cluster formation in lithium chloride (LiCI) and titanium tetrachloride (TiCI4) - Mazibuko, Andile Faith (My University, 2021)
Titanium is the most abundant element in the earth’s crust and can be produced as both a metal and in powder form. It finds applications in various industries such as in medical and aerospace, where the fabrication of components with excellent corrosion and high temperature performance are significant. This metal also plays a significant role in the titanium production process due to its desirable physical and chemical properties. However, this process occurs in the presence of alkali metal and alkali earth metal salt mediums. In this study, a combination of computational modelling techniques was employed to investigate the LiCl, TiCl, TiCl2 and TiCl4 systems and their interaction with titanium cluster (Ti7) at various temperatures. The density functional theory-based codes were used to study the structures and stability, while the classical force-fields codes were employed to study the temperature effect on these systems. Firstly, the LiCl model was validated using Buckingham interatomic potentials from the Catlow-library, employing the GULP code. The selected potential parameters were able to reproduce the LiCl structure to within 1% in agreement with experimental data. Furthermore, the Ti-Cl and Ti-Li interatomic potential parameters from accurate first principle calculations describe the interaction of LiCl and Ti7 cluster. The new interatomic potential parameters were deduced as Ti-Cl: 𝐷𝑒= 0.400, 𝑎0= 1.279, 𝑟0=2.680 and Ti-Li: 𝐷𝑒 =0.730, 𝑎0=1.717, 𝑟0=2.000. vi Secondly, DL_POLY code was used to characterise both the bulk LiCl and Ti7/LiCl structures employing rigid ion and shell models. It was found that the diffusion coefficient of LiCl was 6.26 nm2 /s, which corresponds to the melting temperature range of 700 K – 800 K for the rigid ion model. This agrees well with the experimental melting temperature range of 877 K – 887 K. The shell model predicts a lower melting temperature range of 600 K – 700 K at a diffusion coefficient of 3.74 nm2 /s, compared to rigid ion model. This behaviour was confirmed by the broadness of peaks on the RDF graphs at this temperature. The RDF graphs for the Ti7/LiCl structure in both rigid ion model and shell model depict a change in the morphology of the system for all interactions as the temperature is increased. It was found that the shell model is preferential for the LiCl structure. Thirdly, the elastic and mechanical properties of the TiCl, TiCl2 and TiCl4 structures were evaluated. It was found that the TiCl2 and TiCl4 structures are elastically unstable. However, the mechanical properties indicated that TiCl2 and TiCl4 are mechanically stable. The TiCln structures, namely TiCl and TiCl2, were evaluated for rigid ion model, to check the transferability of potentials. It was found that the diffusion coefficient of TiCl was 32.02 nm2 /s, which corresponds to a melting temperature of 700 K. The diffusion coefficient for TiCl2 was 115.00 nm2 /s at a melting temperature of 800 K. Lastly, molecular dynamics calculations carried out on the Ti7/TiCln structure showed that an increase in temperature results in the broadening of peaks and a decrease in the peak heights. The entropy and Gibbs formation free energy for LiCl (rigid ion and shell models), vii TiCl and TiCl2 (rigid ion model) structures were estimated to determine the influence of temperature on the structures. It was found that the LiCl (shell model) structure is stable at all temperatures and that the TiCl and TiCl2 structures are favoured at lower temperatures (< 500 K). These results provided new insight into understanding the reactions and interactions of titanium clusters with salt mediums in titanium production processes. Moreover, the findings may contribute towards developing alternative ways of titanium production in continuous and less expensive processes.
Thesis (M. Sc. (Physics)) -- University of Limpopo, 2021
Keywords: Lithium cluster; Titanium Tetrachloride (TiCI4); Density; Temperature; Titanium tetrachloride; Lithium chloride; Titanium